Contribution to a ranking procedure for polymeric caotings and hydrophobic agents for concrete - Aguiar, J. L. Barroso de (2008)
One of the possible ways to protect the concrete is using coatings and hydrophobic agents that act as a barrier against the environment. When selecting the material for concrete protection, importance should be given to these properties of diffusion and permeability. The coatings and the hydrophobic agents must stop the penetration of water and delay the influence of aggressive agents, allowing the structure to breathe by a water vapour diffusion mechanism. An evaluation of the surface layer transport properties gives information on the durability of a particular concrete. In order to make the selection of coatings and hydrophobic agents for concrete protection, it is important to analyse the compound’s technical and economical performances. A ranking procedure, developed by Czarnecki and Lukowski, is applied on a series of concrete protection products. The ranking procedure is applied to evaluate durability experiments, carried out on some commercially available silicone, acrylic and epoxy compounds for surface treatment of concrete. The ranking procedure transforms experimental data of properties into one numerical value, by which the products can be classified according to the way on which their properties present an optimised or even best buy combination. The paper shows the use of the ranking procedure methodology, and points at the importance of the choice of the criteria and of their relative weight factor in the evaluation. The method is a valuable tool for the ranking of similar materials, whose performance is based on the same or similar physical or chemical processes.